2020
DOI: 10.1097/btf.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anatomic Relationship Between Sural Nerve and Instrumentation During Mini-Open Achilles Tendon Repair: A Cadaveric Study

Abstract: The purpose of this study was to determine the relationship of the sural nerve to the Arthrex Percutaneous Achilles Repair System (PARS) jig and repair sutures. We performed cadaveric dissection on 10 unpaired above-knee amputation specimens (6 were right legs and 4 were left legs). In all but 1 cadaver, all of the sutures either punctured the nerve or passed anterior to it. Only 1 cadaver had sutures that were posterior to the sural nerve. In all cases, removal of the jig pulled the sutures through the nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A main concern in minimally invasive techniques is the risk of damage or entrapment of the sural nerve, especially when grasping the proximal stump percutaneously, with no direct visualization of the nerve. Krautmann et al 7 evaluated the anatomic relationship between the sural nerve and percutaneous instrumentation with the Percutaneous Achilles Repair System (Arthrex Inc., Naples, FL) and identified that the nerve was punctured 18% of the times (4 of 10 specimens), although in all cases the removal of the jig pulled the sutures through the nerve and the nerve was freed again.…”
Section: Historical Perspectivementioning
confidence: 99%
“…A main concern in minimally invasive techniques is the risk of damage or entrapment of the sural nerve, especially when grasping the proximal stump percutaneously, with no direct visualization of the nerve. Krautmann et al 7 evaluated the anatomic relationship between the sural nerve and percutaneous instrumentation with the Percutaneous Achilles Repair System (Arthrex Inc., Naples, FL) and identified that the nerve was punctured 18% of the times (4 of 10 specimens), although in all cases the removal of the jig pulled the sutures through the nerve and the nerve was freed again.…”
Section: Historical Perspectivementioning
confidence: 99%